Surface roughness effect on rotor broadband noise. Issue 4 (July 2018) - Cheng, Baofeng; Han, Yiqiang; Brentner, Kenneth S; Palacios, Jose; Morris, Philip J; Hanson, David; Kinzel, Michael
The change of helicopter rotor broadband noise due to different surface roughness during ice accretion is investigated. Comprehensive rotor broadband noise measurements are carried out on rotor blades with different roughness sizes and rotation speeds in two facilities: the Adverse Environment Rotor Test Stand facility at The Pennsylvania State University, and the University of Maryland Acoustic Chamber. In both facilities, the measured high-frequency broadband noise increases significantly with increasing surface roughness height. Rotor broadband noise source identification is conducted and the broadband noise related to ice accretion is thought to be turbulent boundary layer-trailing edge noise. Theory suggests turbulent boundary layer-trailing edge noise scales with Mach number to the fifth power, which is also observed in the experimental data confirming that the dominant broadband noise mechanism during ice accretion is trailing edge noise. A correlation between the ice-induced surface roughness and the broadband noise level is developed. The correlation is strong, which can be used as an ice accretion early detection tool for helicopters, as well as to quantify the ice-induced roughness at the early stage of rotor ice accretion. The trailing edge noise theories developed by Ffowcs Williams and Hall, and Howe both identify two important parameters: boundary layer thickness and turbulence intensity. Numerical studies of two-dimensional airfoils with different ice-induced surface roughness heights are conducted to investigate the extent that surface roughness impacts the boundary layer thickness and turbulence intensity (and ultimately the turbulent boundary layer-trailing edge noise). The results show that boundary layer thickness and turbulence intensity at the trailing edge increase with the increased roughness height. Using Howe's trailing edge noise model, the increased sound pressure level of the trailing edge noise due to the increased displacement thickness and normalized integrated turbulence intensity are 6.2 and 1.6 dB for large and small accreted ice roughness heights, respectively. The estimated increased sound pressure level values agree reasonably well with the experimental results, which are 5.8 and 2.6 dB for large and small roughness height, respectively.